Faktor-Faktor yang Mempengaruhi Efikasi Diri Ibu Menyusui di Dusun 1, Desa Tanjung Anom - Citra Dewi Fitri; Nafi’atul Latifah (STIKES Columbia Asia Medan, 2024)
Exclusive breastfeeding is important for the quality of children's health. However, the proportion of exclusive breastfeeding at the Deli Serdang City Health Center has only reached 45.6%, still far from the World Health Organization (WHO) target of 50%. Nurse self-efficacy is one of the important elements that influences nursing behavior. This study aims to determine factors related to breastfeeding self-efficacy. This research was cross-sectional, with a sample of 147 mothers obtained by purposive sampling. Breastfeeding Self-Efficacy (BSE) was measured using the Breastfeeding Self-Efficacy Short-Form. Data analysis used the Chi-Square test. The results of the study showed that there was a significant relationship between breastfeeding problems (p value=0.001), family support (p value=0.001), and support from health workers (p value=0.001) with breastfeeding self-efficacy. It was concluded that breastfeeding problems, family support, and support from health workers were factors related to breastfeeding self-efficacy in breastfeeding mothers. Therefore, health workers and families are expected to provide support to mothers when they have breastfeeding problems.